A STRUCTURED PHYSICAL ACTIVITY AND HEALTH CARE EDUCATION BEATS POSTPARTUM DEPRESSION FOR PRIMIPARA MOTHERS: A PILOT RANDOMIZED CONTROLLED TRAIL (International Journal of Physiotherapy, 2014)
Background: First time mothers in particular may feel anxious about how they are going to cope with looking after themselves and their newborn. Most Indian women believe that they have little or no control over their pregnancies or outcomes. The aim of this study was to evaluate the effect of a Structured Physical Activity and Health Care Education program on the psychological well-being for Primipara mothers in postpartum period.Methods: This study was a Randomized Controlled Trail. Primipara mothers who were ready for discharge from The Narayana Medical College & General Hospital in postnatal ward were eligible for this study. Forty one (41) Primipara mothers randomized onto the trail. The experimental group(n=20) received an 4 week “Structured Physical Activity” (SPA) program, including Structured Physical Activity provided by a team of health care professionals combined with parenting education & counseling. The other group (n=21) Health Care Education Only (HCEO) received only the same educational material as the experimental group. In pre and post schedule outcome measures of both SPA&HCEO groups were assessed with Psychological well-being (Positive Affect Balance Scale), Depressive symptoms (Edinburgh Postpartum Depression Scale), and Physical activity were assessed at baseline, 4th week and then 8th week later.Results: The improvement was significantly high in well-being scores, depressive symptoms and physical activity of the (SPA) group compared with the (HCEO) group over the study period and this effect was maintained 8 weeks after completion of the program.Conclusion: A Structured Physical Activity and Health Care Education program is effective in improving the well-being for Primipara mothers in postpartum period. Continuous use of this program may reduce long-term problems such as postpartum depression and it will change the women’s Physical, emotional and social health.